EFFECT OF SHIN’ISEIHAITO ON LUNG COLONIZATION OF PNEUMOCOCCUS IN MURINE MODEL - Minami, Masaaki; konishi, Toru; Jiang, Zhixia; Arai, Tetuya; Makino, Toshiaki (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Streptococcus pneumoniae (pneumococcus) causes various serious diseases including sinusitis, pneumonia, and meningitis. One serious problem observed recently with pneumococcal therapy is attenuation of the antibiotic effect because of the emergence of antibiotic-resistant pneumococcus. Shin’iseihaito, a traditional Japanese medicine based on ancient Chinese medicine, has been used for treatment of otolaryngeal diseases in Japan. The objective of this study was to examine the anti-infectious effects of shin’iseihaito and its related mechanism. Materials and Methods: We evaluated the beneficial effect of shin’iseihaito extract (SSHT) against pneumococcus-infected murine model. The colonization of bacteria, blood and bronchoalveolar lavage (BAL) killing activity, the levels of inflammatory cytokine and IgA were investigated. Results: The pneumococcus from blood was not found in both SSHT-treated mice and untreated mice. However, the pneumococcal colonization of lung was significantly (p<0.05) lower after SSHT administration compared with untreated mice. Blood bactericidal assay showed that no significant difference (p=0.07) was observed in the anti-bacterial effect between SSHT-treated mice and untreated mice. However, BAL bactericidal assay showed that the survival rate of pneumococcus using the BAL from SSHT-treated mice was significantly (p<0.05) lower than that using the BAL from untreated mice. We also found increased levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IgA in pneumococcus-infected mice treated with SSHT. Conclusions: SSHT decreased the colonization rate after pneumococcal infection and up-regulated BAL bactericidal activity through modulation of inflammatory cytokines and IgA. Our data also suggest SSHT may be useful for the treatment of pneumococcal infection.